Effect of Land Use Change on Soil Physico-chemical Characteristics in Sungai Batang, east part of Maninjau Caldera - Yulnafatmawita, Yulnafatmawita; Refdinal, Refdinal; Armansyah, Armansyah; Haris, Zainal Abdul (UNIVERSITY OF LAMPUNG, 2022)
Land-use change from the forest to others will affect the soil’s physicochemical properties. The research was conducted to identify soil physicochemical properties affected by land-use change in Sungai Batang, the east-south part of Maninjau caldera. The research used a survey method from which soil was sampled at four different types of land use (forest, bushland, mixed garden, and paddy soil) at 0-30 cm depth with three replicates. The results show that the soil in Sungai Batang was still developing. It was indicated by coarse soil texture (clay loam to sandy clay loam). Land-use change from the forest to other uses has altered some soil physicochemical properties. It increased soil bulk density and decreased total soil porosity, permeability rate, SOM content, and total-N. However, there was an increase in soil characteristics, especially soil P-availability, CEC, Ca- and Na-exchangeable . While the soil pH (H2O), K-and Mg-exchangeable stayed the same. In general, land use changed from forest to other use, mostly farming land degraded physicochemical characteristics of the soil derived from volcanic materials in Sungai Batang. That was mainly due to the decrease in SOM content.